A generalized self-consistent approach to study position-dependent mass in semiconductors organic heterostructures and crystalline impure materials - El-Nabulsi, Rami Ahmad (Physica. E, Low-dimensional systems & nanostructures, 2020)
The purpose of this study is to generalize the Coordinate Integral Transform recently introduced in literature for the self-consistent solution of Schrödinger equation in one-dimensional systems with position-dependent mass. It was revealed that the present generalized approach reveals several motivating properties in material sciences and may be used to model and solve a large number of problems arising in solid state sciences ranging from semiconductors heterostructures to organic semiconductors and crystalline solids subject to impurities. •The Coordinate Integral Transform approach for position-dependent mass appraoch is generalized.•A generalized Schrödinger equation is obtained.•The new theory is suitable to describe a large family of semiconductors heterostructures, organic and impure materials.•Enhancement of ground energy levels is revealed.